The Effects of Mandatory Profit-Sharing on Workers and Firms: Evidence from France - Nimier-David, Elio; Sraer, David; Thesmar, David (Quarterly Journal of Economics, 2026)
Abstract Since 1967, all French firms with more than 100 employees have been required to share a fraction of their excess profits with their employees. Through this scheme, firms with excess profits distribute, on average, 10.5% of their pretax income to workers. In 1990, the eligibility threshold was reduced to 50 employees. We exploit this regulatory change to identify the effects of mandated profit-sharing on firms and their employees. The cost of mandated profit-sharing for firms is evident in the significant bunching at the 100-employee threshold observed prior to the reform, which completely disappears post-reform. Using a difference-in-differences strategy, we find that at the firm level, mandated profit-sharing (i) increases the labor share by 1.8 percentage points, (ii) reduces the profit share by 1.4 percentage points, and (iii) has small to nonexistent effects on investment and productivity. At the employee level, mandated profit-sharing increases lower-skilled workers’ total compensation and leaves high-skilled workers’ total compensation unchanged. Overall, mandated profit-sharing redistributes excess profits to lower-skilled workers in the firm without generating significant distortions or productivity effects.